ANALYSIS OF FACTORS AFFECTING EMPLOYEE PERFORMANCE AT BANK SYARIAH INDONESIA (BSI) OF ADAM MALIK BRANCH OFFICE IN MEDAN CITY - Farida Hanum; M Ihsan Harahap (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2022)
This study aims to determine the concept of factors that affect employee performance at Bank Syariah Indonesia (BSI), which expected to be empowering human resources, work motivation, job satisfaction. A study of human resource management (HR) literature. The type of research used by the researcher is field research using qualitative methods and literature studies or library research. Data collection techniques used by researchers are interviews and observation. The finding reveals that HR empowerment has an effect on employee performance at Bank Syariah Indonesia, Work motivation has an affects employee performance at Bank Syariah Indonesia, and Job satisfaction has an effect on employee performance at Bank Syariah Indonesia. Therefore, the findings means that the more often the empowerment of human resources is given, the higher the employee's performance and the higher the work motivation, the higher the employee's performance and will also result in job satisfaction for employees at Bank Syariah Indonesia (BSI) Adam Malik Branch Office in Medan City.